2001
DOI: 10.1089/105072501316973127
|View full text |Cite
|
Sign up to set email alerts
|

Radioiodine Ablation of Thyroid Remnants After Preparation with Recombinant Human Thyrotropin

Abstract: Radioiodine ablation (RA) of normal thyroid remnants after thyroidectomy for differentiated thyroid carcinoma improves the sensitivity of subsequent radioiodine scans and serum thyroglobulin measurements for detection of residual thyroid carcinoma. Local cancer recurrences are also lower after RA. One standard preparation for RA involves rendering the patient hypothyroid in order to stimulate endogenous thyrotropin (TSH) secretion and sodium iodide symporter (NIS) activity. An alternative approach is to prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0
9

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 20 publications
2
45
0
9
Order By: Relevance
“…This may include severe lethargy and fatigue,while enabling patients to remain euthyroid (7)(8)(9)(10). In addition, a multi-centre, randomised, controlled trial has directly compared the use of rhTSH preparation with the standard hypothyroid preparation, prior to remnant ablation with an activity of 3.7 GBq 131 I (11).…”
Section: Introductionmentioning
confidence: 99%
“…This may include severe lethargy and fatigue,while enabling patients to remain euthyroid (7)(8)(9)(10). In addition, a multi-centre, randomised, controlled trial has directly compared the use of rhTSH preparation with the standard hypothyroid preparation, prior to remnant ablation with an activity of 3.7 GBq 131 I (11).…”
Section: Introductionmentioning
confidence: 99%
“…The patient is placed back on levothyroxine suppressive therapy, as appropriate, and approximately 1 week after the treatment dose of RAI, a post-therapy WBS is performed to better assess for residual or metastatic disease. Substitution of rhTSH stimulation for TSH stimulation by THW for diagnostic evaluations (shown in Figure 2b and reviewed by Cooper et al (2006) or for thyroid remnant ablation (shown in Figures 1c and 1d), has been published by a number of centers, allowing patients to remain on levothyroxine therapy and avoid the symptoms of hypothyroidism (Robbins et al 2001;Robbins et al 2002b;Barbaro et al 2003;Barbaro et al 2006;Pacini et al 2006a;Pilli et al 2007;Rosario et al 2008;Taieb et al 2008;Tuttle et al 2008). Over the last 3 years, thyrotropin alfa (Thyrogen ® ) has been approved for RAI ablation by the United States Food and Drug Administration (FDA, 2007), in Europe (2005), and in certain Asian (2007) and South American countries (2006).…”
Section: Management Issues In Thyroid Cancer and Use Of Radioiodinementioning
confidence: 99%
“…Although a traditional method of preparation for the high-dose radioiodine therapy is thyroid hormone withdrawal (THW), nowadays, recombinant human thyroidstimulating hormone (rh-TSH) is increasingly used instead. It has also been proposed that rh-TSH stimulates iodine uptake via activation of the sodium-iodine symporter and leads to sufficient I-131 uptake in thyroid remnants to allow for complete remnant ablation [5].…”
Section: Introductionmentioning
confidence: 99%